INVERSION RULES AFTER NEGATIVE ADVERBS: COMPLIANCE IN MODERN ENGLISH - Rakhmatilloeva, Rukhshonabonu (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article examines the syntactic phenomenon of subject-auxiliary inversion following negative adverbs in contemporary English. Through corpus analysis and examination of both formal and informal discourse, this study investigates the extent to which speakers and writers adhere to prescriptive inversion rules. The research reveals that while inversion remains a productive grammatical feature in formal written English, its application varies considerably across registers, with notable deviations in spoken and digital communication contexts.